Microfluidics-based selection of red-fluorescent proteins with decreased rates of photobleaching. Issue 2 (5th December 2014) - Dean, Kevin M.; Lubbeck, Jennifer L.; Davis, Lloyd M.; Regmi, Chola K.; Chapagain, Prem P.; Gerstman, Bernard S.; Jimenez, Ralph; Palmer, Amy E.
Abstract : We use a high-throughput microfluidic platform that sorts cells on the basis of fluorescent protein photostability to identify a new variant with improved photon output. Abstract : Fluorescent proteins offer exceptional labeling specificity in living cells and organisms. Unfortunately, their photophysical properties remain far from ideal for long-term imaging of low-abundance cellular constituents, in large part because of their poor photostability. Despite widespread engineering efforts, improving the photostability of fluorescent proteins remains challenging due to lack of appropriate high-throughput selection methods. Here, we use molecular dynamics guided mutagenesis in conjunction with a recently developed microfluidic-based platform, which sorts cells based on their fluorescence photostability, to identify red fluorescent proteins with decreased photobleaching from a HeLa cell-based library. The identified mutant, named Kriek, has 2.5- and 4-fold higher photostability than its progenitor, mCherry, under widefield and confocal illumination, respectively. Furthermore, the results provide insight into mechanisms for enhancing photostability and their connections with other photophysical processes, thereby providing direction for ongoing development of fluorescent proteins with improved single-molecule and low-copy imaging capabilities.